The effects of design-based art activities on students’ spatial thinking skills - Dilmaç, Sehran; Dilmaç, Oğuz (International Journal of Evaluation and Research in Education (IJERE), 2025)
This study was conducted to determine the effects of design-based learning (DBL) on students’ spatial thinking skills in architectural design education. Spatial thinking skills are of great importance in the architectural design process for architecture students to perceive and comprehend both the surrounding architectural spaces and the architectural product they design from different dimensions and perspectives. In order to gain this skill, DBL approaches based on a cooperative learning approach, which allow students to actively participate in the learning process, were applied. It was tested whether the DBL approach would increase students’ spatial thinking skills and develop skills, such as visual structuring skills, creativity, multidimensional and abstract thinking skills, imagination, problem solving, and multi-function execution. The research model is a pre-test-post-test control group quasi-experimental design. Data were obtained using the spatial thinking skills test. Based on the findings obtained as a result of the research, it was determined that the DBL approach applied in the color and texture course was effective on the spatial thinking skills of 2nd-year architecture students.